A systematic review of romantic relationship initiation and maintenance factors in autism. Issue 4 (9th August 2021) - Yew, Rui Ying; Samuel, Priscilla; Hooley, Merrilyn; Mesibov, Gary B.; Stokes, Mark A.
Abstract: Autistic individuals report similar levels of interest in romantic relationships to their nonautistic peers but experience greater challenges with the initiation and maintenance of these relationships. This systematic review synthesizes the factors that contribute to romantic relationship initiation and maintenance among autistic individuals to inform relationship support programs. Both successes (e.g., ability to initiate relationships and maintain a satisfying relationship) and challenges (e.g., relationship dissatisfaction) were investigated. Out of 1403 potentially relevant articles, 11 articles comprising 13 studies met the inclusion criteria (investigated factor[s] of romantic relationship success of challenges, involved participants with a formal autism diagnosis and/or their partners, presented quantitative results in relationship factors, and was available in an English‐language version). Social and communication challenges were studied to the greatest extent and were associated with difficulties in both relationship initiation and satisfaction. Several factors relating to the partner of the autistic individual were associated with successful relationships, including reciprocal liking, partner support, and the ability to meet the autistic partner's needs. Conclusions are limited by the small number of studies but provide initial indications that social and communicative factors, as well as the role of nonautistic partners, are important to the success of romantic relationships for autistic individuals. In keeping in line with the community's preference for identity‐first language (i.e., "autistic individual" rather than "individual with autism"), this language has been used throughout this review.